Export spillovers from foreign direct investment: Evidence from Turkey - Başak Dalgıç; Burcu Fazlıoğlu; Michael Gasiorek (Turkish Economic Association, 2015)
This paper explores export spillovers that arise from foreign direct investment generated linkages between domestic and foreign firms in Turkish manufacturing industry. By making use of a recent firm level dataset, we investigate how supplying to foreign affiliated firms, as proxied by their presence in downstream industries and foreign presence in firms' own industry affects (i) extensive and intensive margins of domestic firms' exporting, (ii) the quality of exports proxied by unit values, (iii) the decision of domestic firms to export or start exporting, (iv) firms' export orientation towards destination markets with high income levels. The results of the study suggest that even after controlling for firm heterogeneity, stronger presence of foreign firms in downstream industries yields better export performance of domestic firms. We do not find any evidence on the effect of supplying to foreign affiliated firms on the quality of exporting. Furthermore, it is shown that foreign presence in downstream industries is associated with higher probability of exporting, while foreign presence in firms' own industry is found to have a negative effect. Finally, we find evidence on the fact that supplying to multinationals in downstream industries is positively associated with firms' both intensive and extensive margins of exports towards developed regions of the world.
Keywords: D22; F14; F23; 330; FDI; Export Spillovers; Extensive Margin; Intensive Margin